An Analysis of the Medico-Legal Aspects and Trends in Sexual Offense Cases at a Tertiary Care Hospital - Dhuvaraga R.; Dipayan Deb Barman; N. Karthikeyan (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: Women and children represent the most vulnerable groups to sexual assault, resulting in profound physical and psychological trauma. The increasing frequency of sexual offenses globally has become a serious medico-legal and public health concern. Objective: To analyse the demographic profile, social aspects, examination findings, and medico-legal trends of sexual assault cases reported to a tertiary care hospital. Methods: A prospective study was conducted on 60 sexual assault cases reported to the Department of Forensic Medicine & Toxicology at Govt.Chengalpattu Medical College Hospital. Data from medico-legal cases were analysed for age, religion, literacy, socio-economic status, marital status, place of incidence, time of reporting, relationship with assailant, and genital findings. Results were expressed as frequencies and percentages. Results: The majority of victims were young unmarried females (86.67%) from low socio-economic backgrounds (88.33%). Most assaults occurred at the victim’s residence (60%), with the assailant often being a neighbour (56.67%). Medical examination was conducted within 1–3 days in 70% of cases. Hymenal tears were found in 96.67% of victims, with recent tears (30%), old tears (41.67%), and carunculae myrtiformes (25%) being the major findings. Conclusion: Sexual offenses predominantly affect young, economically disadvantaged women, with the assailant usually known to the victim. Strengthening medico-legal reporting, forensic training, and community awareness are essential to improve justice outcomes and victim rehabilitation.